Aktivitas antioksidan ekstrak bunga telang (Clitoria ternatea L.) dan aplikasinya dalam sediaan serum - Selly Harnesa Putri; Hasyyati Nadhilah; Dian Juliadmi; Asri Widyasanti (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
The unhealthy lifestyle of Indonesians can increase the amount of free radicals that have an impact on skin health. Free radicals can be prevented by increasing antioxidants derived from telang flower (Clitoria ternatea L.). The purpose of this study was to determine the antioxidant activity and phytochemical screening results of telang flower extract and to determine the effect of adding extract in serum gel preparation. Telang flower extract was obtained through maceration process using 96% ethanol solvent in a ratio of 1:10 for 2x24 hours. Antioxidant activity was tested using DPPH (1,1-diphenyl-2-picrylhydrazil) method. Data analysis was performed using One Way Anova test method followed by Duncan's Multiple Range Test (DMRT) with 95% confidence level. Telang flower extract is positive for flavonoids, saponins, triterpenoids, and tannins with an IC50 value of 53.546 ppm. The IC50 value of serum gel preparations with formulations F0, F1, F2, F3, F4, F5 consecutively amounted to 261.847 ppm, 91.294 ppm, 82.748 ppm, 74.487 ppm, 72.041 ppm, 66.985 ppm. The pH value of the serum gel preparation is in the range of 5.70 - 7.38 with a viscosity value of 581.33 - 1625 mPas and no irritation reaction on the skin. Based on the results of the study, it can be concluded that the higher the concentration of telang flower extract, the higher the antioxidant activity in serum gel preparations.